KETELADANAN GURU AKIDAH AKHLAK DALAM MEMBINA AKHLAK PESERTA DIDIK - Nurlela (Tadzkirah : Jurnal Pendidikan Dasar, 2020)
This study examines the moral creed of exemplary teachers in fostering morals learners in Graphic Teknika SMK Kartika Gadingrejo Gadingrejo District of the Academic Year 2018/2019. The data analysis technique used is descriptive qualitative, ie, to collect data and then organize the data that appears to be presented, and the conclusions are drawn - checking the validity of the data using data triangulation techniques. Compare data from direct observations with data from interviews and detailed results. The results obtained are exemplary moral theology teacher in the moral development of students in graphic Teknika SMK Kartika Gadingrejo Gadingrejo District of Academic Year 2018/2019 already looks good. Excellent teachers do that is by applying the creed of ethical ideals, discipline, familiarize greetings, get used to praying, spiritual direction, and co-operation of teachers with parents. Based on the results obtained, it can be concluded, with exemplary teachers creed akhlak in fostering morals, learners already look well. It is marked by increasing discipline, courtesy, responsibility, honesty, forgiveness, mutual help, independent, sincere, respectful of others, tawadhu 'and the patient who previously has been observed.